THE EFFECT OF ADDITIONAL DRUGS OF Salted FISH AND MAS (Pomacea canaliculata Lamarck) ON INCREASING THE NUMBER OF QUEEN DUCK EGGS USING RAL METHOD - Darnianti Darnianti (Universitas Quality, 2022)
Ratu Duck is a hybrid duck, which is produced from crosses of MA (Mojosari x Alabio) ducks, which is one type of poultry that has the potential to produce eggs. Efforts to increase the egg production of queen ducks need to use the addition of egg-laying stimulants and feed that is high in protein. To meet protein requirements, gold snails are given as a source of high protein and breast milk fish pulp as a stimulant for laying eggs. This study aims to determine the effect of adding salted fish pulp and gold snails to the increase in the number of duck egg yields. Implemented in Brastagi, for 14 days. The research material included 10 queen ducks aged 24 weeks with an average body weight of 1490.61 ± 107.47 g. The experimental design used was a completely randomized design (CRD) with a unidirectional pattern with four treatments consisting of four replications, each replication consisting of five stimulant queen ducks consisting of salted fish dregs and gold snails. The treatments included P0 (salted fish pulp + 0% gold snail as a control), P1 (salted fish pulp + 3 % gold snail), P2 (salted fish pulp + 6% gold snail) and P3 (salted fish pulp + gold snail 9 %). The variables observed during the study included the number of eggs, egg color, egg white index, egg yolk index and egg yolk weight. ). The results of this research will be published in the Sinta indexed Accredited Journal.